2015
DOI: 10.1007/s12026-015-8648-y
|View full text |Cite
|
Sign up to set email alerts
|

Profound blockade of T cell activation requires concomitant inhibition of different class I PI3K isoforms

Abstract: PI3K inhibitors have emerged as potential therapeutic tools for a variety of diseases, and thus, a vast array of compounds with specificity for different PI3K isoforms is being developed. Gaining knowledge about the contribution of the different isoforms to PI3K function will allow selecting the most appropriate inhibitor for each pathology. In this study, we have addressed the effect of PI3K inhibitors with specificity for different class I PI3K isoforms on primary human T cell activation. In particular, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
4
6
0
Order By: Relevance
“…As PI3Kδ is widely expressed in leucocytes it is unknown whether this results from effects on the CLL cells, T cells, non-T cells or a combination of these. In agreement with other reports [53] neither caffeine nor Idelalisib affected the proliferation of PBMC cultured alone. It has been reported that broad PI3K inhibition can increase the susceptibility of T cells to suppression by cells such as Tregs [54].…”
Section: Discussionsupporting
confidence: 93%
“…As PI3Kδ is widely expressed in leucocytes it is unknown whether this results from effects on the CLL cells, T cells, non-T cells or a combination of these. In agreement with other reports [53] neither caffeine nor Idelalisib affected the proliferation of PBMC cultured alone. It has been reported that broad PI3K inhibition can increase the susceptibility of T cells to suppression by cells such as Tregs [54].…”
Section: Discussionsupporting
confidence: 93%
“…In line with the Akti results, functional inhibition of PI3Kd by use of the specific pharmacological PI3Kd inhibitor Cal also reduced T allo proliferation. Thereby, a relatively high Cal concentration, which has been described previously to broaden the PI3Kd inhibitory effect also on the other PI3Kd [20], was necessary to achieve a considerable suppression of T allo proliferation, indicating that selective PI3Kd inhibition might be compensated, at least in parts, by activity of other PI3Kd, as already demonstrated for antigen-mediated cytokine production and proliferation of T cells [43,44]. Taken together, our results demonstrate an impact of PI3K/Akt activity on T allo proliferation in vitro but also indicate that neither Akt 1/2 nor PI3Kd inhibition alone might be sufficient for a substantial depletion of T allo in aGvHD patients and thus, suggest combination approaches.…”
Section: Discussionsupporting
confidence: 64%
“…On the other hand, BKM120 and BEZ235 induced a dose-dependent decrease in Th1/Th2 cytokine secretion, according to studies performed with PI3K [ 10 , 12 ] and mTOR inhibitors [ 28 , 29 ]. Once more, BEZ235 was more potent than BKM120 at intermediate doses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that the beneficial effects observed in patients with chronic GvHD treated with tyrosine kinase inhibitors could be due, in part, to their ability to inhibit PI3K signaling in T cells [ 9 ]. However, few studies have evaluated the immunosuppressive effect of PI3K inhibitors on T lymphocytes [ 10 12 ] and their ability to prevent GvHD development [ 13 , 14 ]. Herein, we have analyzed the effects of two novel antitumor drugs, the pan-class I PI3K inhibitor BKM120 and the dual PI3K/mTOR inhibitor BEZ235, on T cell activation and evaluated the utility of BEZ235 in a murine model of GvHD.…”
Section: Introductionmentioning
confidence: 99%